Effect of Product Presentation Videos on Consumers' Purchase Intention: The Role of Perceived Diagnosticity, Mental Imagery, and Product Rating - Cheng, Zhendong; Shao, Bingjia; Zhang, Yong (Frontiers in Psychology, 2022)
The product presentation videos on the E-commerce platforms have a significant influence on consumers' purchase decisions and enterprises have focused on choosing the type of product presentation videos. Based on the resource matching theory, mental imagery theory and cue utilization theory, this study investigated the influence of product presentation videos type (product appearance video vs. product usage video) on consumers' purchase intention and the moderating effect of product rating (low vs. high). Through three pre-experiments and two formal experiments, the results showed that the product usage video have a stronger effect on consumers' purchase intention more than the product appearance video, which is mediated by perceived diagnosticity and mental imagery. In addition, product rating moderated the influence of product presentation videos type on consumers' purchase intention. The product usage video would improve consumers' purchase intention more than the product appearance video when the product rating is high, however, there is no significant difference in the impact of two types of videos on consumers' purchase intention when the product rating is low. This study supplements the research on product presentation videos and provides a reference for online retailers to select the effective product presentation videos.